2020
DOI: 10.1128/aac.02263-19
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analyses for Omadacycline Using Phase 1 and 3 Data

Abstract: Omadacycline, a novel aminomethylcycline antibiotic with activity against Gram-positive and -negative organisms, including tetracycline-resistant pathogens, received FDA approval in October 2018 for the treatment of patients with acute bacterial skin and skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP). A previously developed population pharmacokinetic (PK) model based on phase 1 intravenous and oral PK data was refined using data from infected patients. Data from 10 phase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Once protein binding estimates were accounted for (approximately 21% and approximately 80% for omadacycline and tigecycline, respectively), the total drug ELF to unbound serum penetration ratios were 1.84 for omadacycline and 6.59 for tigecycline [94]. Lakota and colleagues conducted a population PK analysis for omadacycline using the same omadacycline ELF data and plasma concentration-time data from phase I and III clinical research studies [95]. The total drug ELF to unbound plasma penetration ratio based on AUC 24 values at day 4 of therapy was calculated to be 2.06.…”
Section: Omadacycline and Tigecyclinementioning
confidence: 99%
“…Once protein binding estimates were accounted for (approximately 21% and approximately 80% for omadacycline and tigecycline, respectively), the total drug ELF to unbound serum penetration ratios were 1.84 for omadacycline and 6.59 for tigecycline [94]. Lakota and colleagues conducted a population PK analysis for omadacycline using the same omadacycline ELF data and plasma concentration-time data from phase I and III clinical research studies [95]. The total drug ELF to unbound plasma penetration ratio based on AUC 24 values at day 4 of therapy was calculated to be 2.06.…”
Section: Omadacycline and Tigecyclinementioning
confidence: 99%
“…Previous PK modelling has not identified high BMI or diabetes as covariates of interest, which potentially negates this concern. 22 , 23 Finally, this analysis was based on well-defined study populations that may not reflect all patient populations that are treated with these antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…All participants received a loading dose of omadacycline (300 mg orally twice on Day 1), followed by maintenance treatment of 300 mg orally once daily (qd), for a total treatment duration of 7–10 days [ 10 ]. The loading dose was selected to closely match the reference IV regimen for bioequivalence: 100 mg IV given twice on Day 1, the FDA-approved IV loading dose for both CABP and ABSSSI [ 1 , 2 , 7 , 10 , 11 ].…”
Section: Background On Omadacycline Oral Regimensmentioning
confidence: 99%
“…Previous studies have shown that there was no significant interaction of omadacycline with a broad range of membrane transporters, suggesting that drug–drug interactions based on the inhibition or induction of human drug transporter activity are unlikely with omadacycline when given at therapeutic concentrations [ 7 , 14 ]. The bioavailability of oral omadacycline is 34.5%; omadacycline is not metabolized, and oral omadacycline is primarily eliminated in the feces [ 4 , 7 , 11 , 15 ]. Previous Phase 1 and Phase 3 studies of omadacycline showed that no dose adjustments are necessary for any patient group, such as people with hepatic or renal impairment, including end-stage renal disease (ESRD) and those receiving dialysis [ 4 , 6 , 13 ]; dose adjustments are also unnecessary by body mass index [ 13 , 16 , 17 ] or older age [ 1 ].…”
Section: Pharmacokinetics Of Omadacyclinementioning
confidence: 99%